Engineering and Development of VP4-VP7 Rotavirus Fusion Protein in Pichia pastoris - Mostafa Amopour Bahnamiry (Vaccine Research, 2020)
Introduction: Vaccination is the most effective measure to prevent Rotavirus infection in children under five years of age. The most important targets of neutralizing and protective antibodies against this virus are VP4 and VP7 proteins of Rotavirus. Today, the recombinant protein produced in yeast plays an important role in producing highly effective and cost-effective vaccines. Methods: The effect of different linkers, including flexible and rigid, were evaluated on the stability and immunogenicity of the protein via in silico assays. A suitable linker was selected and expressed in Pichia pastoris yeast. Prediction and validation were carried out using bioinformatics tools, including Expasy's ProtPara, Phyre2 online server, I-TASSER server, ElliPro. Moreover, an appropriate linker was selected for cloning into pPICZα and expression in P. pastoris. Results: The results showed that as a flexible linker, (GGGGS)3 was the best structure to provide stability for VP4-VP7 target fusion protein. The produced recombinant protein was stable after the expression. Conclusion: These in silico results and expression data on P. pastoris suggested that VP4–(GGGGS)3-VP7 construct can potentially serve as a potent immunogenic candidate for recombinant Rotavirus vaccines.